Strategi Harian Serambi Indonesia dalam Mempertahankan Eksistensi Surat Kabar di Era Media Baru - Muzakkir muzakir; Ritayani ritayani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The challenges of print media in the current technological era are growing rapidly. The era where the role of technology is increasingly influencing the dissemination of information that spreads online and offline. This study aims to determine the strategies used by the print media of the Serambi Indonesia daily newspaper in maintaining its existence in the new era or the digital era. This study uses a qualitative descriptive analysis method with one informant. Data collection techniques through interviews and documentation. The author found the results of this study regarding the strategy carried out by the Serambi Indonesia daily print media, namely being selective in the selection of news content by approaching schools. Participating in the Tribun group, Serambi Indonesia joined together into local newspaper groups throughout Indonesia. Serambi Indonesia also carries out media convergence by creating online media, radio and social media. The choice of news that deserves to be published in the newspaper is accurate news, and the news presented has accurate content that does not cause irony or hoaxes. Therefore, the Serambi Indonesia Daily newspaper is still needed by many people and it is also still in great demand by the public compared to online media. Harian Serambi Indonesia remains a proud newspaper and also a trust in the hearts of the people, even making it the oldest newspaper that still exists in the era of the birth of new media in the development of technology in Indonesia.